KRAS targeting antibody synergizes anti-cancer activity of gemcitabine against pancreatic cancer. (1st December 2018) - Kang, Yeo Wool; Lee, Ji Eun; Jung, Kyung Hee; Son, Mi Kwon; Shin, Seung-Min; Kim, Soo Jung; Fang, Zhenghuan; Yan, Hong Hua; Park, Jung Hee; Han, Boreum; Cheon, Min Ji; Woo, Min Gyu; et al.
Abstract: Pancreatic cancer exhibits an oncogenic KRAS mutation rate of ∼90%. Despite research and drug development efforts focused on KRAS, no targeted therapy has been clinically approved for the treatment of pancreatic cancer with KRAS mutation. Also, the efficacy of gemcitabine is poor due to rapidly acquired resistance. We developed RT11-i antibody, which directly targets the intracellularly activated GTP-bound form of oncogenic RAS mutants. Here, we investigated the combined effects of RT11-i and gemcitabine in vitro and in vivo, and the mechanism involved. RT11-i significantly sensitized pancreatic cancer cells to gemcitabine. Also, the co-treatment synergistically inhibited angiogenesis, migration, and invasion, and showed synergistic anticancer activity by inhibiting the RAF/MEK/ERK or PI3K/AKT pathways. Furthermore, co-treatment inhibited endothelial barrier disruption in tumor vessels, which is a critical step in vascular leakiness of metastasis, and improved vessel structural stability. Importantly, co-treatment significantly suppressed tumor growth in an orthotopic tumor model. Taken together, our findings show that RT11-i synergistically increased the antitumor activity of gemcitabine by inhibiting RAS downstream signaling, which suggests RT11-i and gemcitabine be viewed a potential combination treatment option for pancreatic cancer patients with KRAS mutation. Highlights: Pancreatic cancer exhibits an oncogenic KRAS mutation rate of ∼90%. KRAS gene silencing increased gemcitabine sensitivity in pancreatic cancer. RT11-i antibody directly targets the intracellularly activated GTP-bound form of RAS after being internalized into cytosol. RT11-i significantly sensitized pancreatic cancer cells to gemcitabine, as evidenced by reduced cell growth. The co-treatment showed synergistic anticancer activity by inhibiting the RAF/MEK/ERK or PI3K/AKT pathways. RT11-i and gemcitabine could be a potential combination treatment option for pancreatic cancer patients with KRAS.